OPTIMAL LOCATION OF OPTIMIZED FRICTION DAMPERS IN CIVIL STRUCTURES FOR THE SEISMIC PASSIVE CONTROL - Ontiveros-Pérez, Sergio Pastor; Fadel Miguel, Letícia Fleck; Fadel Miguel, Leandro Fleck (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents a methodology to improve installation of friction dampers in civil structures. The proposed methodology involves a metaheuristic optimization technique called Firefly Algorithm linked with a computational routine based in the Finite Differences Method to carry out the simultaneous optimization of the friction forces and positions of friction dampers. The proposed method is illustrated in a ten-story shear building, that is, the method finds the best stories to locate the dampers with optimal mechanical parameters. The objective function used in this study is to minimize the maximum inter-story drift of the tenstory shear building, which is located in Cúcuta, Colombia. For this purpose, the authors used the NSR-10 (Colombian Seismic Code).